Frequency and etiology of pulmonary hypertension in patients with myeloproliferative neoplasms. (10th January 2019) - Brabrand, Mette; Hansen, Knud Nørregaard; Laursen, Christian B.; Larsen, Thomas Stauffer; Vestergaard, Hanne; Abildgaard, Niels
Abstract: Objective: Pulmonary hypertension (PH) has been reported to be associated with myeloproliferative neoplasms (MPN), affecting 5%‐48% of MPN patients. With the aims to describe the prevalence of PH in Ph‐MPN patients and explore the cause in identified subjects, we performed a prospective cohort study of Ph‐MPN patients. Method: Transthoracic echocardiography (TTE) was performed on all patients. When the TTE was abnormal, further investigations were performed according to current guidelines from the European Society of Cardiology. The primary endpoint was the frequency of PH. The secondary endpoint was causes of PH. Results: We included 158 patients, median age was 65 years. Fifty percent had polycythemia vera, 34% essential thrombocytosis, and 11% primary myelofibrosis, 3% post‐ET‐myelofibrosis, and 2% post‐PV‐myelofibrosis. Only six patients (3.8%) were found to have a high probability of PH. They were all examined with right heart catheterization and all met the invasive criteria for PH. In all six patients other causes than MPN for PH were identified, although some contribution from the MPN could not be ruled out in three patients. Conclusion: In the largest study ever reported, we found a lower prevalence of PH (3.8%) than previously reported. Screening for PH in unselected MPN patients is not justified.